2017
DOI: 10.1111/josi.12247
|View full text |Cite
|
Sign up to set email alerts
|

Race and Reaction: Divergent Views of Police Violence and Protest against

Abstract: Since 2012, the United States has seen a renewed focus on police killings of racial and ethnic minorities, as well as protest against such violence. Moreover, recent polling data show an intensification of long-standing differences in Black and White Americans' attitudes toward police violence and protest. Here, we review recent polling, as well as our own series of experiments, to elucidate racial divides in attention, attitudes, and reactions to police violence and protest against it (e.g., Black Lives Matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 16 publications
4
68
0
1
Order By: Relevance
“…One hypothesis may be that despite similar acknowledgment of police bias, emotional reactivity to those events is greater for certain historically marginalized populations. In this special issue, Reinka and Leach () found that Black participants had stronger reactions to police violence than White participants, despite greater familiarity with the experience. This may also be viewed through the paradigm of police violence as racial trauma outlined by Bryant‐Davis and colleagues ().…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis may be that despite similar acknowledgment of police bias, emotional reactivity to those events is greater for certain historically marginalized populations. In this special issue, Reinka and Leach () found that Black participants had stronger reactions to police violence than White participants, despite greater familiarity with the experience. This may also be viewed through the paradigm of police violence as racial trauma outlined by Bryant‐Davis and colleagues ().…”
Section: Discussionmentioning
confidence: 99%
“…But these types of descriptions are not an anomaly (see Reinka & Leach, ; Scott, Ma, Sadler, & Correll, for other perceptions of police violence). Take, for instance, posthumous characterizations of Eric Garner, a 43‐year‐old unarmed Black man killed in 2014 by New York City Police officer Daniel Pantaleo.…”
mentioning
confidence: 99%
“…Reinka and Leach (), similarly, found that Blacks and Whites had different degrees of knowledge about police brutality and Black protest. Using open‐ended responses to visual images of police violence and largely Black protests, they found that Whites judged images of Black protest more novel, but that these images mattered more to Blacks.…”
Section: How? the Role Of Attitudes Perceptions And Beliefsmentioning
confidence: 98%
“…What are available response options for an individual who experiences or witnesses violence, whether lethal, merely harassing, or intimidating? Four possibilities are offered: (1) trauma, depression (Bryant‐Davis et al., ); (2) normalization—psychic defense (Nadal et al., ); (3) activism—protest and resistance (Reinka & Leach, ); and (4) learned helplessness—diminished coping and lack of control (Kauff, Wölfer, & Hewstone, ). These analyses provide a broad picture of an expanded set of consequences of police brutality that goes beyond the specifics of a given incident.…”
Section: What? Effects Of Violence On Psyche Body Community and Gementioning
confidence: 99%